ChemInform Abstract: Donharrisite, Ni3HgS3: Crystal Structure and Revision of the Chemical Formula. Issue 35 (August 2016) - Bindi, Luca; Paar, Werner H.
Abstract: The title mineral crystallizes in the monoclinic space group C2/m with Z = 4 (single crystal XRD).